2015
DOI: 10.1063/1.4931908
|View full text |Cite
|
Sign up to set email alerts
|

Structural, dielectric and magnetic properties of nickel substituted cobalt ferrite nanoparticles: Effect of nickel concentration

Abstract: Microstructure and magnetic properties of MFe 2 O 4 (M = Co, Ni, and Mn) ferrite nanocrystals prepared using colloid mill and hydrothermal method Journal of Applied Physics 117, 17A328 (2015) Nickel substituted cobalt ferrite nanoparticles with composition Co 1−x Ni x Fe 2 O 4 (0.0≤x≤1.0) was synthesized using simple, low temperature auto combustion method. The X-ray diffraction patterns reveal the formation of cubic phase spinel structure. The crystallite size varies from 30-44 nm with the nickel content. Por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(48 citation statements)
references
References 39 publications
6
41
0
1
Order By: Relevance
“…Most of the literature only confirm that Jonscher’s power law can be used to describe the electrical conductivity of ferrites [ 27 ]. In their work, Velhal et al showed that electrical conduction can be related to small polarons in cobalt ferrite nanoparticles; however, this result has not been combined with the previously described electrical conduction mechanism associated with hopping of electrons, and has not been confirmed by an analysis of s ( T ) behavior [ 28 ]. Moreover, many works only attributed variations of AC conductivity with frequency to the hopping of electrons between Fe 3+ and Fe 2+ ions and conduction by small polarons, without using the Jonscher’s power law, and determining the conduction mechanism model or hopping energy value [ 15 , 16 , 29 ].…”
Section: Introductionmentioning
confidence: 95%
“…Most of the literature only confirm that Jonscher’s power law can be used to describe the electrical conductivity of ferrites [ 27 ]. In their work, Velhal et al showed that electrical conduction can be related to small polarons in cobalt ferrite nanoparticles; however, this result has not been combined with the previously described electrical conduction mechanism associated with hopping of electrons, and has not been confirmed by an analysis of s ( T ) behavior [ 28 ]. Moreover, many works only attributed variations of AC conductivity with frequency to the hopping of electrons between Fe 3+ and Fe 2+ ions and conduction by small polarons, without using the Jonscher’s power law, and determining the conduction mechanism model or hopping energy value [ 15 , 16 , 29 ].…”
Section: Introductionmentioning
confidence: 95%
“…NCF shows a shift towards higher angles at 57.03 o and 63.11 o correspond to (511) and (440) planes. The shift is due to the smaller ionic radius (0.069 nm) of Ni 2+ , than that of (0.072 nm) Co 2+ , with lower lattice parameter and lattice volume [5]. respectively.…”
Section: Characterizationmentioning
confidence: 93%
“…Considering its good chemical and thermal stability, high electrical resistivity, magnetic anisotropy, high H C , moderate M S , superparamagnetism, ferrimagnetism and dielectric structure, the Ni doped Co ferrite is a good candidate for microwave devices and data storage [71]. The Co 1−x Ni x Fe 2 O 4 (0.0 ≤ x ≤ 1.0) synthesized using simple, low temperature auto-combustion method showed high resistance.…”
Section: Applications Of Dielectric Propertiesmentioning
confidence: 99%
“…The Co 1−x Ni x Fe 2 O 4 (0.0 ≤ x ≤ 1.0) synthesized using simple, low temperature auto-combustion method showed high resistance. As the Ni content increases, the dielectric constant and loss tangent decrease and remain constant at higher frequencies, while conductivity increases with increasing frequency [71]. The use as supercapacitors of mixed ternary Cu-Co-Ni ferrites obtained by sol-gel synthesis and citric acid as chelating agent was investigated by Bhujun et al [72].…”
Section: Applications Of Dielectric Propertiesmentioning
confidence: 99%